Emotional dependence of female victims of intimate partnership violence - Aiquipa Tello, Jesús Joel (2015)
The following study aims to identify the relationship between emotional dependency and intimate partner violence in a sample of women who utilize the psychology service of a national health establishment. A quantitative approach is followed with a comparative associative strategy. The sample consisted of two groups of women, female victims of intimate partner violence (25 women) and women who were not victims of intimate partner violence (26 women). The results suggest that there is a statistically significant relationship between the variables of study, since differences between the two study groups was found and it was found that the value assumed correlation coefficient between variables was highly significant.